Language Planning and Language Ideology: The Majority and Minority Dichotomy in Nepal - Yadav, Raj Narayan (Tribhuvan University Journal, 2013)
Language planning and language Ideology in Nepal have not been really responsive to the linguistic diversity. Nepal is a multiethnic, multi-religious, multicultural, multilingual, federal and democratic-republican country. It has two linguistic lines – linguistic majority and linguistic minority. This paper deals with the language planning and Ideology in Nepal since Panchayat regime to the present. This paper also advocates the strategy for government of governance. It allows for decentralization of power and recognizes and protects the linguistics rights of all Nepalese.